Inventory Optimization of Fresh Agricultural Products Supply Chain Based on Agricultural Superdocking. (24th January 2020) - Shen, Lixin; Li, Fucheng; Li, Congcong; Wang, Yumin; Qian, Xueqi; Feng, Tao; Wang, Cong
Abstract : The "agricultural superdocking" mode which has been strong supported by the government has become the main way for fresh agricultural products to enter the market in China. Based on the analysis of fresh agricultural products supply chain inventory management under the "agricultural superdocking" mode, this paper constructs an integrated inventory model for fresh agricultural products of "farmers' professional cooperatives + distribution centers + supermarkets." Considering multiple members at each echelon of a supply chain, a model that maximizes the overall profit of the supply chain is proposed. The model assumes that the market demand of fresh agricultural products is affected by freshness and sales prices, and the distribution center is responsible for not only storage, processing, and distribution but also coordinating the production and supply information of farmers' professional cooperatives and the order sales information of supermarkets. An improved genetic algorithm is developed to solve the nonlinear optimization problem. Results of a case study show that the optimal supply and replenishment strategy under the given supply chain distribution process are obtained.